2003
DOI: 10.1248/bpb.26.1691
|View full text |Cite
|
Sign up to set email alerts
|

New Fluoroprostaglandin F2.ALPHA. Derivatives with Prostanoid FP-Receptor Agonistic Activity as Potent Ocular-Hypotensive Agents

Abstract: An elevated intraocular pressure (IOP) is one of the risk factors for the development of glaucoma. Recent prospective epidermal studies in the United States indicate that if IOP is lowered below 12 mmHg, 1) or by more than 30% from the baseline IOP in patients with normal-tension glaucoma, 2) the progress of the visual field defect can be delayed. Prostaglandin (PG) derivatives exert ocular-hypotensive effects through stimulation of prostanoid receptors (FP, DP, IP etc.) and possibly by activation of signal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 24 publications
3
65
0
1
Order By: Relevance
“…In the case of PGF 2␣ analogs, esterification of the prostaglandin ␣-chain carboxyl group sufficiently increases the lipophilicity of the molecule for it to traverse the cornea and/or sclera, where it is enzymatically hydrolyzed back to the active acid form for delivery to the ocular tissues and fluids (Madhu et al, 1998). In accord with such findings, the present studies have demonstrated that the novel 15,15-difluorinated PGF 2␣ ocular hypotensive agent tafluprost (Nakajima et al, 2003) acts as an efficient prodrug for tafluprost acid when applied topically to the eyes of albino rats, just as it does with related compounds such as latanoprost (Sjöquist et al, 1998). Hydrolysis of the ester to the pharmacologically active acid was both rapid and complete after ocular administration of tafluprost: the tritiated prodrug was not detected in eye tissues or plasma by radio-HPLC, whereas the acid form was effectively the only radioactive component in the cornea, aqueous humor, and iris/ciliary body for at least 8 h postdose.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the case of PGF 2␣ analogs, esterification of the prostaglandin ␣-chain carboxyl group sufficiently increases the lipophilicity of the molecule for it to traverse the cornea and/or sclera, where it is enzymatically hydrolyzed back to the active acid form for delivery to the ocular tissues and fluids (Madhu et al, 1998). In accord with such findings, the present studies have demonstrated that the novel 15,15-difluorinated PGF 2␣ ocular hypotensive agent tafluprost (Nakajima et al, 2003) acts as an efficient prodrug for tafluprost acid when applied topically to the eyes of albino rats, just as it does with related compounds such as latanoprost (Sjöquist et al, 1998). Hydrolysis of the ester to the pharmacologically active acid was both rapid and complete after ocular administration of tafluprost: the tritiated prodrug was not detected in eye tissues or plasma by radio-HPLC, whereas the acid form was effectively the only radioactive component in the cornea, aqueous humor, and iris/ciliary body for at least 8 h postdose.…”
Section: Discussionsupporting
confidence: 74%
“…Recent studies with 15-monofluorinated-and 15,15-difluorinated prostanoids showed that replacement of the hydroxyl group on that position with the halogen atom(s) can increase the desired FP-receptor-related activities while decreasing the side effects (Nakajima et al, 2003). Tafluprost [1-methylethyl (5Z)-7-{(1R,2R,3R,5S)-2-[(1E)-3,3-difluoro-4-phenoxy-1-butenyl]-3,5-dihydroxycyclopentyl}-5-heptenoate] (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Он сочетает в себе максимальную эффективность (снижение внутриглазного дав-ления до 35 % при режиме дозирования один раз в сутки) с высоким профилем безопасности. Его молекула обладает бо льшим сродством к FP-рецепторам, что не только обес печивает более вы-раженный гипотензивный эффект, но и снижает выраженность местных побочных явлений, таких как гиперемия конъюнктивы и гиперпигмента-ция кожи век и радужной оболочки [22,28,33]. Есть данные о наличии у тафлупроста нейропро-текторного действия [34].…”
Section: Doi: 1017816/ov9259-68unclassified
“…Consequently, these prostanoids are used in patients with glaucoma as the first-line of therapy. In addition to marketed prostanoids, another new prostanoid with FP-receptor agonist activity, tafluprost, will become available in the near future (33,34,37,56). A low incidence of systemic side effects is one of the reasons for the widespread use of prostanoids in the therapy of glaucoma.…”
Section: Introductionmentioning
confidence: 99%